Recent advances in applying identity and society awareness to virtual learning - Stricker, Andrew; Calongne, Cynthia; Truman, Barbara; Arenas, Fil J. (IGI Global, 2019)
"This book addresses new ways of thinking in the use of 3D design thinking and cognitive apprenticeship in virtual learning spaces for team science, transdisciplinarity, idea development, and curation"--